INKUBASI INDUSTRI MIKRO DAN BADAN USAHA MILIK NAGARI DI NAGARI SUNGAI KAMUYANG - Donard Games; Dessy Kurnia Sari (LPPM Universitas Andalas, 2021)
Incubation becomes a necessity to improve the performance of micro and small industries. Products from Nagari Sungai Kamuyang have the potential to be further developed. However, there is no incubation process that systematically and provides input in innovation strategies that can improve organizational performance. This activity aims to provide a platform for the industry to improve innovation strategies and organizational performance. In this activity, three small and micro industries become tenants or incubates the rendang business, the jengkol yam cracker business, and the various cake businesses. In addition, incubation was also carried out at Nagari Sungai Kamuyang Enterprises to improve organizational performance through the role of this institution to strengthen micro and small industries in Sungai Kamuyang Nagari. The incubation was carried out by Andalas University Management Study Program lecturers from various disciplines, namely financial management, entrepreneurship, marketing management, and human resource management. The activities obtained are for the economic empowerment of Nagari Sungai Kamu, which requires growing micro and small businesses. This activity is carried out by coaching and mentoring by lecturers directly with three business actors. The result is comprehensive input from various disciplines, and this is sustainable by providing a discussion process (coaching and mentoring). The three micro-businesses that become the incubation tenants have problems in standardization, marketing, product innovation, business strategy, and overall business management. The activities carried out by PSM have attempted to incubate by dividing lecturers with various tenant skills. It is hoped that there will be recommendations and other processes that can evaluate and follow up on these recommendations.